Soluble mesothelin in effusions: a useful tool for the diagnosis of malignant mesothelioma. Issue 7 (13th March 2007) - Creaney, Jenette; Yeoman, Deborah; Naumoff, Leanne K; Hof, Michelle; Segal, Amanda; Musk, Arthur William; De Klerk, Nicholas; Horick, Nora; Skates, Steven J; Robinson, Bruce W S
Abstract : Background: The diagnosis of malignant mesothelioma is frequently difficult, the most common differential diagnosis being reactive pleural conditions and metastatic adenocarcinoma. Soluble mesothelin levels in serum have recently been shown to be highly specific and moderately sensitive for mesothelioma. As most patients with mesothelioma present with exudative effusions of either the pleura or the peritoneum, a study was undertaken to determine if levels of mesothelin were raised in these fluids and if the increased levels could help to distinguish mesothelioma from other causes of exudative effusion. Methods: Pleural fluid was collected from 192 patients who presented to respiratory clinics (52 with malignant mesothelioma, 56 with non-mesotheliomatous malignancies and 84 with effusions of non-neoplastic origin). Peritoneal fluid was collected from 42 patients (7 with mesothelioma, 14 with non-mesotheliomatous malignancies and 21 with benign effusions). Mesothelin levels were determined in effusion and serum samples by ELISA. Results: Significantly higher levels of mesothelin were found in effusions of patients with mesothelioma; with a specificity of 98%, the assay had a sensitivity of 67% comparing patients with mesothelioma and those with effusions of non-neoplastic origin. In 7 out of 10 cases mesothelin levels were raised in the effusion collected 3 weeks to 10 months before the diagnosis of mesothelioma was made; in 4 out of 8 of these, mesothelin levels were increased in the effusion but not in the serum. Conclusions: Measurement of mesothelin concentrations in the pleural and/or peritoneal effusion of patients may aid in the differential diagnosis of mesothelioma in patients presenting with effusions.